Rapid qualitative health research from the Global South: Reflections and learnings from Argentina, Brazil, Chile, and Mexico during the COVID-19 pandemic - Eguiluz, Itzel; Sy, Anahi; Brage, Eugenia; González-Agüero, Marcela (Frontiers in Sociology, 2022)
The objective of this paper is to provide insights into our experiences undertaking qualitative rapid research in Latin American contexts based on fieldwork from Argentina, Brazil, Chile, and Mexico. We focus on the insights and learning processes that emerged from our research teamwork during the COVID-19 pandemic. Our research projects are part of an international collaboration led by the Rapid Research Evaluation and Appraisal Lab (RREAL) to explore the experiences of COVID-19 Frontline Healthcare Workers. The analyzed experiences not only rely on the local studies but also on our reflections as a group of Latin American researchers collaborating along with an international team. Qualitative research has an important and long-lasting tradition in Latin America. However, healthcare professionals are still reluctant to use these methods. We highlight tensions and dilemmas that have emerged from our own empirical experience: First, the time for research ethics committees to evaluate the protocols; second, the difficulties in accessing funding to undertake research due to the lack of financial opportunities; third, having to decide the language of our publications. That is just the tip of the iceberg that allows us to show inequalities in the conditions under which scientific knowledge is produced between the North and the Global South. Following these points, our text explores the tension between the urgency to conduct rapid research and the multiple difficulties when undertaking it during the pandemic. It is important to point out that the problems we faced already existed before the sanitary emergency, being magnified by the former. At last, our conclusions delve into the reflexive process we, as a team of female researchers, undertook to explore the differences and similarities of our experiences. This analysis allowed us to solve obstacles and dilemmas when doing research. The winding road we describe here serves as an example for other research teams when planning and undertaking rapid qualitative research during future pandemics.